Performing Interventions: The Politics and Theatre of China’s AIDS Crisis in the Early Twenty-First Century - Anderson, Virginia (Viral Dramaturgies, 2017)
Theatrical productions attest to a radical shift in Chinese governmental policy and public awareness of the AIDS epidemic at the dawn of the twenty-first century; state-subsidised theatre worked directly with the government to contain the transmission of HIV. Produced by two of the country’s most elite cultural institutions, the Shanghai Dramatic Arts Center and the Beijing People’s Art Theatre respectively, The Dying Kiss (Shengsi Zhiwen) in 2003 and Student Zhao Ping (Zhao Ping Tongxue) in 2005 represented a sea change in the political response to the epidemic while documenting public perceptions towards people living with HIV and AIDS in China. Marking policy change, they reflect experiences that capture a society transitioning from denial to confrontation at the dawn of the twenty-first century.